Moo, moo, brown cow, have you any milk? - Gershator, Phillis (Random House Children's Books, 2011)
Through rhyming text, farm animals are asked if they have items needed to prepare for a snack and bedtime, such as wool for a blanket, down for a pillow, and milk to drink.